Value - Orientated Approach to the Study of Socio-Economic Problems of the Organization of the Innovation Community - O. R. Chepyuk (Vestnik MGIMO-Universiteta)
The author presents a review of scientific papers and methodological manuals on the researching of innovation community problems. It is stated that different approaches can be applied to analyze national innovation systems and clusters. Special attention is given to the value-based approach. That enables to find out ways and methods how to build a high effective innovation system and social-stable innovation community.